1990
DOI: 10.1046/j.1537-2995.1990.30891020334.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA, GM, KM, and Diego blood group typing of Chippewa Indians

Abstract: This is the first report characterizing HLA antigen distribution in North American Indians of the Chippewa tribe. One hundred seventy-four Chippewa from Minnesota underwent HLA-A,B,C,DR, and DQ typing in a search for a single unrelated bone marrow donor. The high matching rate of this successful search is attributed to homozygosity and the extreme frequency of certain antigens in this small ethnic community. It is emphasized that smaller donor pools are required in searches within a minority population. GM and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Finally, we were unable to compare HLA frequencies in our AB DESRD subjects with an optimal AB control population such as matched healthy subjects without a high risk for T2DM and renal disease; however, identifying such individuals might be very difficult. The fact that other North American Indian populations are also known to have high frequencies of A2, A24, DR4 and DR8 [32, 33]lends support to the sobering possibility that large proportions of these populations may have a genetic propensity to develop T2DM and its complications.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we were unable to compare HLA frequencies in our AB DESRD subjects with an optimal AB control population such as matched healthy subjects without a high risk for T2DM and renal disease; however, identifying such individuals might be very difficult. The fact that other North American Indian populations are also known to have high frequencies of A2, A24, DR4 and DR8 [32, 33]lends support to the sobering possibility that large proportions of these populations may have a genetic propensity to develop T2DM and its complications.…”
Section: Discussionmentioning
confidence: 99%
“…The calculated gene frequencies were 0.05-0.08 for Dia and 0.92-0.96 for Dib. l8 In 1990 a study by Lee et al 19 showed that Diego typing of the Chippewa tribe in Minnesota had patterns similar to those reported in other North American Indian populations.…”
Section: History and Anthropological Studiesmentioning
confidence: 72%